Awaruite, a new large nickel resource. Part 2: Assessment of magnetic separation. (January 2023) - Seiler, Santiago; Sánchez, Gustavo; Bradshaw, Peter; Klein, Bern
Highlights: Nickel recovery increases at higher magnetic field strengths. Magnetic separation recovers over 90% of the magnetic nickel. Nickel losses are associated with fine and very fine awaruite. Abstract: In this work, a research study, focused on the recovery of awaruite, was conducted on a representative sample from the Baptiste deposit to evaluate magnetic separation over a range of magnetic field strengths. The Baptiste deposit is a unique nickel deposit containing awaruite, a high-density ferromagnetic nickel–iron alloy. The evaluation included semi-batch and continuous pilot scale tests, employing wet magnetic drums at two different grind sizes. The samples were characterized using techniques including chemical composition analysis, Davis tube testing, and automated mineral analysis. The results showed promising magnetic nickel recoveries, in the range of 92% to 96%. The development of the Baptiste deposit will benefit from a sound scientific understanding of the process solution.